2011
DOI: 10.2116/analsci.27.105
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Derivatization of Xanthurenic Acid and Nicotinic Acid with Horseradish Peroxidase in the Presence of Excess Hydrogen Peroxide

Abstract: The fluorescent derivatization of tryptophan metabolites (xanthurenic acid, nicotinic acid, picolinic acid, and 3-hydroxyanthranilic acid) by the catalytic activity of horseradish peroxidase (HRP) was investigated in the presence of excess H2O2. Non-fluorescent xanthurenic acid (XA) and nicotinic acid (NA) were converted into a fluorescent compound with maximum excitation and emission wavelengths at 325 and 425 nm, and 318 and 380 nm, respectively. This fluorescent derivatization was developed for the fluorome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
(38 reference statements)
0
3
0
2
Order By: Relevance
“…Enzyme activity was then confirmed through an enzyme cascade reaction between HRP and GOX. When hydrogen peroxide is present, HRP can modify numerous substrates in solution , including fluorescent substrates and Amplex Red. This reporter molecule may be used to quantify enzymatic activity or hydrogen peroxide concentration .…”
Section: Resultsmentioning
confidence: 99%
“…Enzyme activity was then confirmed through an enzyme cascade reaction between HRP and GOX. When hydrogen peroxide is present, HRP can modify numerous substrates in solution , including fluorescent substrates and Amplex Red. This reporter molecule may be used to quantify enzymatic activity or hydrogen peroxide concentration .…”
Section: Resultsmentioning
confidence: 99%
“…1), all of which are aromatic carboxylic acids, are converted fluorescent compounds by the catalytic activity of HRP in the presence of excess H2O2. [4][5][6] In this study, we further investigated the action of HRP in the presence of excess H2O2 on various aromatic carboxylic acids shown in Fig. 1 to determine whether such activity, as previously demonstrated, would yield fluorescent compounds.…”
Section: Ah2 + H2o2 →mentioning
confidence: 90%
“…Previously, we demonstrated that non-fluorescent tryptophan metabolites, such as nicotinic acid (1b), quinolinic acid (2a), kynurenic acid (8a), and xanthurenic acid (8b), were converted into fluorescent compounds by the catalytic activity of HRP in the presence of excess H2O2. [4][5][6] So, the fluorescent derivatization of various non-or weakly fluorescent aromatic carboxylic acids in Fig. 1 was investigated in the presence of excess H2O2.…”
Section: Fluorescent Derivatization Of Non-or Weakly Fluorescent Arommentioning
confidence: 99%
“…En el caso de la detección por fluorescencia, usualmente se añade acetato de zinc en post-columna para mejorar la señal [187][188][189][190] , aunque en otro método se empleó la detección de fluorescencia inducida por láser [191] . El KYNA también ha sido analizado directamente por espectrofluorimetría previa derivatización con peroxidasa de rábano (HRP) en presencia de peróxido de hidrógeno [192][193][194] , o por reacción fotoquímica post-columna con peróxido de hidrógeno [195] . También se ha determinado KYNA por detección UV [196,197] , o espectrofotometría después de la derivación con ácido sulfanílico diazotizado [198] , y con menor frecuencia usando NMR [199] , o la espectrometría de masas [77,[200][201][202] .…”
Section: Vi2 Antecedentes Bibliográficos Para El Análisis De Triptóunclassified
“…Dada la falta de estudios sobre la determinación simultánea de estos compuestos en miel, y que la mayoría de los trabajos se realizan en matrices biológicas [77,[187][188][189][190][191][192][193][194][195][196][197][198][199][200][201][202][203] , se ha desarrollado un método de cromatografía de líquidos con detección de diodos…”
Section: Vi2 Antecedentes Bibliográficos Para El Análisis De Triptóunclassified